Unprepared : America in the time of coronavirus - Sternfeld, Jon (Bloomsbury Publishing, 2020)
A chronicle of the COVID-19 pandemic as it unfolded gathers statements from President Trump and other elected officials, leading journalists, and scientists to offer a portrait of the confusion, drama, and fear that defined the outbreak.